2020
DOI: 10.1186/s13643-020-01329-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the prevalence of gaming disorder and Internet gaming disorder: a rapid scoping review

Abstract: Background: Internet gaming disorder (IGD) was included in the DSM-5 in 2013 as a condition requiring further research, and gaming disorder (GD) was included in the ICD-11 in 2018. Given the importance of including these conditions in diagnostic guidelines, a review was conducted to describe their prevalence. Methods: Using guidance from the Joanna Briggs Institute and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR), we conducted a rapid scoping… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 13 publications
1
82
0
Order By: Relevance
“…However, some susceptible people lose control over gaming as a leisure activity, resulting in negative consequences, such as Internet gaming disorder (IGD). Approximately 0.21–57.50% of people have IGD [ 2 ]. The Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM-5) first included IGD as a research criterion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some susceptible people lose control over gaming as a leisure activity, resulting in negative consequences, such as Internet gaming disorder (IGD). Approximately 0.21–57.50% of people have IGD [ 2 ]. The Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM-5) first included IGD as a research criterion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence estimates of IGD among general samples have been always below 5% ( 7 , 8 ), with a low of 0.5% and a high of 10% ( 9 ). In recent meta-analysis studies, the global prevalence of IGD was reported to be about 3.05% with significant variability ( 10 ), ranging from 0.21 to 57.5% in general populations, 3.2–91.0% in clinical populations, and 50.42–79.25% in populations undergoing intervention (i.e., severe cases) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subscales of the SCL-90, with the exception of phobic anxiety, were completed by respondents with internet gaming disorder, but none was found to increase susceptibility to internet gaming disorder in this study. The prevalence of internet gaming disorder has previously been found to range between 0.27% and 57.50% [34] and that of internet addiction has been found to range from 0.8% to 26.7% [35]. Notably, prior studies [5,[36][37][38][39][40][41] indicated that internet addiction and video game addiction or problematic gaming prevalence dropped within the older age groups.…”
Section: Prevalence and Demographics Of Internet Gaming Disorder Amonmentioning
confidence: 98%